Formulation Of Pipe-Reducing Paste (Blushon) Using Young Jati Leaf Extract (Tectona Grandis L.F) As Natural Dye - Novrita, Sisri; Audry Reji Renata Griffin; Revi Yenti; Larysa Fernenda (JFARM - Jurnal Farmasi, 2024)
Young teak leaves (Tectona Grandis L.f) contain anthocyanin pigments which can give a red color. Utilization of anthocyanin pigments can be used as natural dyes. The purpose of this study was to formulate a blush paste preparation using young teak leaf extract (Tectona grandis l.f) as a natural dye. This study uses an experimental method. The extraction method for teak leaf dyes uses the maceration method. In this study, 3 formulas for blush on were prepared in the form of pastes with various concentrations of 2.0%, 2.5% and 3% thick extract of teak leaves. Then a physical evaluation of the blush preparation was carried out which included organoleptic, homogeneity, pH, spreadability, irritation, hedonic, and stability tests. Based on the organoleptic tests carried out, it indicates that there is a change in color and stability is not good. The results of the spreadability test did not meet the standards and the results of the homogeneity test and the pH test showed that there were no coarse grains then the pH test was around 6 (according to the general skin pH interval) and did not cause irritation so it was safe to use on the skin. The results of the physical evaluation of the blush paste from young teak leaf extract met the standards. So teak leaf extract (Tectona grandis l.f) can be formulated as a blush paste. The results of the hedonic test showed that the blush paste using young teak leaf extract (Tectona grandis l.f) with a concentration of 2% was the most preferred by the panelists.